Prediction of success at UK Specialty Board Examinations using the mandatory postgraduate UK surgical examination. Issue 6 (30th September 2019) - Scrimgeour, D. S. G.; Cleland, J.; Lee, A. J.; Brennan, P. A.
Abstract : Background: While performance in other mandatory examinations taken at the beginning of a doctor's career are predictive of final training outcomes, the influence early postgraduate surgical examinations might have on success at Specialty Board Exams in the UK is currently unknown. The aim was to investigate whether performance at the mandatory Membership of the Royal College of Surgeons (MRCS) examination, and other variables, are predictive of success at the Fellowship of the Royal College of Surgeons (FRCS) examination, thus potentially identifying those who may benefit from early academic intervention. Methods: Pearson correlation coefficients examined the linear relationship between both examinations and logistic regression analysis identified potential independent predictors of FRCS success. All UK medical graduates who attempted either section of FRCS (Sections 1 and 2) between 2012 and 2018 were included. Results: First attempt pass rates for Sections 1 and 2 FRCS were 87.4 per cent ( n = 854) and 91.8 per cent ( n = 797) respectively. In logistic regression analysis, sex (male: odds ratio (OR) 2.32, 95 per cent c.i 1.43 to 3.76), age (less than 29 years at graduation: OR 3.22, 1.88 to 5.51), Part B MRCS attempts (1 attempt: OR 1.77, 1.08 to 3.00), Part A score (OR 1.14, 1.09 to 1.89) and Part B score (OR 1.06, 1.03 to 1.09) were independent predictors of Section 1 FRCS success. Predictors of Section 2 FRCS success were age (less than 29 years at graduation: OR 3.55, 2.00 to 6.39), Part A score (OR 1.06, 1.02 to 1.11) and Section 1 FRCS score (OR 1.13, 1.07 to 1.18). Conclusion: Part A and B MRCS performance were independent predictors of FRCS success, providing further evidence to support the predictive validity of this mandatory postgraduate exam. However, future research must explore the reasons between the attainment gaps observed for different groups of doctors. Abstract : We aimed to investigate whether MRCS and other variables are predictive of FRCS success. Performance at Part A and B MRCS were found to be independent predictors of FRCS success, providing further evidence to support the predictive validity of this mandatory postgraduate exam. Passing first time predicts future success Abstract : Antecedentes: Si bien el resultado obtenido en otros exámenes obligatorios efectuados al inicio de la formación médica son predictores de los resultados finales obtenidos al terminar la etapa de formación, se desconoce la influencia que podrían tener los resultados de primeros exámenes quirúrgicos de postgrado en el éxito de los exámenes de la Comisión de Especialidad del Reino Unido. El objetivo fue investigar si los resultados obtenidos en el examen obligatorio para ser miembro del Real Colegio de Cirujanos ( membership of the Royal College of Surgeons, MRCS) y de otras variables son predictores de éxito en el examen de ingreso de licenciados universitarios del Real Colegio de Cirujanos ( Fellowship of the Royal College of Surgeons, FRCS), de modo, que fuera posible identificar a aquellos colectivos de cirujanos que podrían beneficiarse de una acción formativa temprana. Métodos: Se utilizaron los coeficientes de correlación de Pearson para evaluar la relación lineal entre ambos exámenes, y un análisis de regresión logística para identificar posibles variables predictivas de éxito del examen del FRCS. Se incluyeron todos los graduados médicos del Reino Unido que intentaron cualquier sección del FRCS (secciones 1 y 2) entre los años 2012 y 2018. Resultados: Al primer intento, las tasas de superación de las secciones 1 y 2 del FRCS fueron del 87, 4% ( n = 854) y del 91, 8% ( n = 797), respectivamente. En el análisis de regresión logística, el sexo (masculino, razón de oportunidades, odds ratio, OR 2, 32, i.c. del 95% 1, 43‐3, 76), la edad (menos de 29 años en el momento de la graduación, OR 3, 22, 1, 88‐5, 51), el número de intentos para superar la Parte B del MRCS (un intento, OR 1, 77, 1, 08‐3, 00) y la puntuación obtenida en las Partes A (OR 1, 14, 1, 09‐1, 89) y B del MRCS (OR 1, 06, 1, 03‐1, 09), fueron predictores independientes de éxito en la Sección 1 del FRCS. Los factores predictivos del éxito en la Sección 2 del FRCS fueron la edad (menos de 29 años a la graduación, 3, 55, 1, 88‐5, 51), la puntuación de la Parte A del MRCS (1, 06, 1, 02‐1, 11) y la puntuación de la Sección 1 del FRCS (1, 13, 1, 07‐1, 18). Conclusión: Los resultados de las partes A y B del MRCS fueron factores predictivos independientes del éxito del FRCS, lo que supone una evidencia adicional en favor de la validez predictiva de este examen obligatorio de postgrado. Sin embargo, la investigación futura debe explorar las razones entre las diferencias de logros observadas para diferentes grupos de médicos.